Sequencing Critical Moves for Ethical Argumentation Practice: Munāẓara and the Interdependence of Procedure and Agent - Oruç, Rahmi; Üzelgün, Mehmet Ali; Sadek, Karim (Informal Logic, 2023)
The aim of this paper is to highlight an interdependence between procedural and agential norms that undermines their neat separation when appraising argumentation. Drawing on the munāẓara tradition, we carve a space for sequencing in argumentation scholarship. Focusing on the antagonist’s sequencing of critical moves, we identify each sequence’s corresponding values of argumentation: coalescence, reliability, and efficacy. These values arise through the mediation of virtues and simultaneously underpin procedural as well as agential norms. Consequently, an ambiguity between procedure and agent becomes apparent. This ambiguity hints at the potential for a virtue theory of argumentation that draws on procedural norms.